In Research of School Resiliency or What Does a Good School Represent in a Digital Society? - Vinogradov, Vladislav; Shatunova, Olga; Merzon, Elena; Sheymardanov, Shamil (Frontiers in Education, 2022)
The role of education as a vertical mobility channel in the digital society engenders the need to assess schools on a “better or worse” scale, both from the perspective of parents (which school should we take our child to?) and education authorities (what measures should be taken?). It is proposed to take the resiliency indicator as a basis for assessing the status of a school, which characterises its ability to ensure the pupils’ results exceeding those expected, with regard for the challenging social context of educational activities and the troubled social structure of the learners’ body. At the same time, the school’s high resiliency ratio does not necessarily secure its high rating positions. Conversely, high rating positions do not condition high extent of the resiliency of the educational organisation. It is proposed to use, as the main indicators pointing at school resiliency, the stability of educational results of schoolchildren for at least three years and the ratio of the school’s absolute rating, which does not take into account the conditions of its functioning, versus its rating with regard for deprivation. The above markers in their totality point to the quality of the school’s educational activities which allows it to achieve better results than in other schools in similar conditions. The research results show that school resiliency in the context of the digitalization of education is determined not by specifics of its strategy, but by qualitative characteristics of its educational activity.